Strategies to Enhance Students’ Self-Confidence in Performing Forward Rolls: A Study of Grade 10 Nursing Assistant Class 2 at Samarinda Health Vocational School - Rafli Awaluddin Azzuhri; Muhammad Sukron Fauzi; Aulia Az-Zahra (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to describe teachers’ strategies in improving students’ self-confidence in performing the forward roll in Class X Nursing Assistant 2 at a Health Vocational High School in Samarinda. The background of this study is based on the low level of self-confidence among some students in performing the forward roll, as indicated by fear, hesitation, and a lack of courage to attempt the movement independently. This condition affects the effectiveness of the learning process and outcomes in Physical Education, Sports, and Health (PE), particularly in floor exercise materials. This study employed a qualitative approach with a descriptive research design. The research subjects included PE teachers and students of Class X Nursing Assistant 2. Data were collected through observation, in-depth interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing and verification. The results indicate that teachers’ strategies in enhancing students’ self-confidence include providing motivation and positive reinforcement, demonstrating movements clearly and progressively, applying cooperative learning methods, using individualized approaches, and offering affective feedback that emphasizes students’ effort and courage. The challenges faced by teachers include differences in students’ physical abilities, fear of injury, and limited self-confidence in attempting movements. To address these challenges, teachers create a safe and supportive learning environment, modify the level of movement difficulty, and provide gradual guidance. Based on the findings, it can be concluded that the implementation of appropriate, psychologically oriented teaching strategies can improve students’ self-confidence in performing the forward roll. Increased self-confidence leads students to become more courageous, active, and motivated in participating in PE learning.